2018
DOI: 10.1007/s10120-018-0879-x
|View full text |Cite
|
Sign up to set email alerts
|

The Cholegas trial: long-term results of prophylactic cholecystectomy during gastrectomy for cancer—a randomized-controlled trial

Abstract: Background The incidence of cholelithiasis has been shown to be higher for patients after gastrectomy than for the general population, due to vagal branch damage and gastrointestinal reconstruction. The aim of this trial was to evaluate the need for routine concomitant prophylactic cholecystectomy (PC) during gastrectomy for cancer. Methods A multicenter, randomized, controlled trial was conducted between November 2008 and March 2017. Of the total 130 included patients, 65 underwent PC and 65 underwent standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 36 publications
0
47
0
1
Order By: Relevance
“…At the initial point of this study, the control group had not been determined because of the difference in indications between LPG and L-TG. It became clear that the postoperative QOL was similar between L-DT and L-JIP, and some researchers have reported that there were few significant differences in the postoperative QOL between total and proximal gastrectomy [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the initial point of this study, the control group had not been determined because of the difference in indications between LPG and L-TG. It became clear that the postoperative QOL was similar between L-DT and L-JIP, and some researchers have reported that there were few significant differences in the postoperative QOL between total and proximal gastrectomy [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many authors recommend performing cholecystectomy simultaneously with gastric cancer surgery for existing gallbladder stones due to concerns about postoperative acute cholecystitis due to gallbladder disease (2,14). In our series, cholecystectomy was performed in 5.9% of patients because of gallbladder disease discovered during gastrectomy, and we did not encounter any complications related to cholecystectomy in these patients.…”
Section: Discussionmentioning
confidence: 64%
“…20 A recent RCT of PC for gastric cancer patients showed that a concomitant PC done during gastric surgery for malignancies is safe and without technical difficulties. 19,53 But the overall postsurgical morbidities of laparoscopic cholecystectomy, including wound infection, bile duct injury, bile leakage, and open conversion are still not negligible. 54 The history of upper abdominal surgery is known as being a risk factor for open conversion of cholecystectomy, 55 although abdominal surgical history is not a risk factor for difficult laparoscopic cholecystectomy for the experienced surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported on the prophylactic effectiveness of UDCA to reduce gallstone formation following gastric surgery in obese patients. [16][17][18][19] Recently, a randomized controlled study (RCT) reported that the results of UDCA administration significantly reduced the incidence of gallstones following gastrectomy for gastric cancer. 20 UDCA is not burdensome to use for prophylactic purpose because it is a well-known, long-term use drug with few severe adverse events.…”
Section: Introductionmentioning
confidence: 99%